2015
DOI: 10.5603/fhc.a2015.0011
|View full text |Cite
|
Sign up to set email alerts
|

PLAGL1 protein is differentially expressed in the nephron segments and collecting ducts in human kidney

Abstract: Introduction. PLAGL1 (pleiomorphic adenoma gene-like 1) is a C2H2-type zinc finger transcription factor associated with the regulation of cell growth and development. Although PLAGL1 expression in kidney was assessed by biochemical methods, the exact localization of the PLAGL1 protein in human kidney has not yet been described. Material and methods. Macroscopically unchanged specimens of kidney tissue were collected from 39 patients undergoing nephrectomy due to renal cell carcinoma. H & E staining of paraffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…IHC, defined as positive immunoreactivity for GAL, was performed as described previously by Godlewski et al (19) with certain modifications. The sections were subjected to antigen retrieval by microwaving for 20 min in retrieval solution buffer (pH 6.0; Leica, Wetzlar, Germany) and incubated with 3% H 2 O 2 in methanol for 10 min followed by 2.5% normal horse serum (Vector Laboratories, Inc., Burlingame, CA, USA) in PBS for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…IHC, defined as positive immunoreactivity for GAL, was performed as described previously by Godlewski et al (19) with certain modifications. The sections were subjected to antigen retrieval by microwaving for 20 min in retrieval solution buffer (pH 6.0; Leica, Wetzlar, Germany) and incubated with 3% H 2 O 2 in methanol for 10 min followed by 2.5% normal horse serum (Vector Laboratories, Inc., Burlingame, CA, USA) in PBS for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, punctual mutations of the PLAGL1 gene were detected in only 71 (0.3%) out of 21,029 tumor samples of all kind registered in the Catalog of Somatic Mutations in Cancer (COSMIC; http://cancer.sanger.ac.uk/cosmic ). To add more complexity, it has been also reported that overexpression of PLAGL1 was detected in some human neoplasms such as glioma and clear cell renal cell carcinoma, suggesting an oncogenic function, as well [ 28 , 29 ]. As regard to HCC, Midorikawa et al found that LOH at the chromosome region 6q24, hypermethylation of PLAGL1 promoter at the remaining allele and low mRNA levels were frequent in tissue samples from patients with hepatoma [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since it was first described, the gene has been considered a tumor suppressor gene (TSG) [ 27 ], and all this evidence provided support for such classification. However, overexpression of PLAGL1 was detected in some human neoplasms such as glioma and clear cell renal cell carcinoma suggesting an oncogenic function, as well [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical (IHC) analysis was performed as described previously by Godlewski et al [ 20 ] with some modification. The sections were subjected to an antigen retrieval procedure by microwaving in Retrieval Solution Buffer (pH 6.0; Leica, Wetzlar, Germany), incubated with 3% H 2 O 2 in methanol for 30 min, and then in commercial normal horse serum (Vector Laboratories, Inc., Burlingame, CA, USA) for 30 min.…”
Section: Methodsmentioning
confidence: 99%